Relationship between Life and Non-Life Insurance and Globalization: Study of Group D8 Countries Using Bootstrap Panel Granger Causality Test - Shahram Fatahi (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2018)
This study investigates the causal linkages between insurance (divided between life and non-life insurance) and globalization in Group D8 countries by focusing on country-specific analysis for the period 1999–2011. For this purpose, we have used the penetration rate of life and non-life insurance and KOF globalization index (as a proxy of globalization) as primary variables. The method used in this study is based on the panel causality test provided by Konya (2006). This method is based on the Seemingly Unrelated Regressions (SUR) model and Wald tests with the country specific bootstrap critical values. Also, this test accounts for cross-dependency and heterogeneity among the members of the panel. Experimental results show that the causality between life and non-life insurance and globalization are not the same in different countries of D8 group, when considering their particular circumstances. For the case of Iran, only a one way causality from the globalization to non-life insurance is verified.